Experts' Awards and Economic Success: Evidence from an Italian Literary Prize - Michela Ponzo; Vincenzo Scoppa (Institute for the Study of Labor (IZA), 2015)
Product quality is often unobservable ex-ante and consumers rely on experts' judgments, sometimes in the form of ratings or awards. Do awards affect consumers' choices or, conversely, are they conferred on the most popular products? To disentangle this issue, we use data about the most important Italian Literary Prize, the "Strega Prize", undertaking two different estimation strategies to evaluate the impact that winning the Prize has on book sales. First, we adopt a Regression Discontinuity Design using a measure of book sales as a dependent variable and as a forcing variable (proxying for intrinsic book quality) the jury votes received by each nominated book in the competition. We find that the Strega Prize has a very strong impact on sales. Second, by using weekly data on appearances on bestseller lists, we estimate a difference-in-differences model in which we compare sales performance of treated and control books before the award is conferred with their respective performances afterwards. The results confirm a huge influence of the Prize on book sales and show that most of the impact occurs in the weeks following the announcement of the Prize.
Keywords: Z10; Z11; L15; L80; M30; D12; J44; 330; cultural economics; awards; asymmetric information; literary prize; book sales; product quality; regression discontinuity design; difference-in-differences model